2013
DOI: 10.1108/amhid-03-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medications and adults with intellectual disabilities: care staff perspectives

Abstract: Purpose -Adults with intellectual disabilities are the most psychotropically medicated population of all. Non-medically trained care staff with whom these individuals spend the majority of their time are generally poorly trained in issues surrounding psychotropic medication. Much of the research related to the experiences of staff working in intellectual disability services has focused on medically trained professionals, and clients, and has been of a quantitative nature. Very little attention has been paid to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Staff felt that they would benefit from training and information about potential triggers to help them think more about environmental conditions and their own role in precipitating BtC. Many other researchers have highlighted support staff frustration for not having the right training and their desire to gather more knowledge and training on (a) mental health issues, (b) medication prescribing (when to use them and why, and when not to use them and why), (c) medication side effects, (d) and when and how medication could be safely withdrawn [ 55 ]. All of these issues are addressed in the SPECTROM programme.…”
Section: Discussionmentioning
confidence: 99%
“…Staff felt that they would benefit from training and information about potential triggers to help them think more about environmental conditions and their own role in precipitating BtC. Many other researchers have highlighted support staff frustration for not having the right training and their desire to gather more knowledge and training on (a) mental health issues, (b) medication prescribing (when to use them and why, and when not to use them and why), (c) medication side effects, (d) and when and how medication could be safely withdrawn [ 55 ]. All of these issues are addressed in the SPECTROM programme.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were generally positive toward the use of psychotropic medication to manage the CB of their family member. This finding conflicts with limited published international evidence that reports on care staff views about psychotropic medication used for CB (Christian et al, 1999;Heslop et al, 2005;Fretwell and Felce, 2007;Lalor and Poulson, 2013); and international and Australian guidance cautions around prescription of psychotropics for this population (Deb et al, 2006(Deb et al, , 2009RANZCP, 2011). However, family members are important advocates and potentially influential decision makers for people with ID/DD (Costello et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Respondents reported "average" medication knowledge, but also indicated a desire for more medication training (Donley et al, 2011). Related findings were described in a qualitative study of eight care staff perspectives supporting adults with ID, where staff reported concerns around the ethical implications of medication use, lack of medication training, and the negative impact of medication on client quality of life (Lalor and Poulson, 2013). In a study conducted in the Netherlands, the majority of support professionals in residential facilities for individuals with ID reported unrealistic expectations about the positive effects of psychotropic medication on client functioning, as well as limited knowledge around psychotropic medication use (de Kuijper and van der Putten, 2017).…”
mentioning
confidence: 84%